Improving the adoption levels of manufacturing strategy formulation processes - Ellson, Tom (Cranfield University, 2002)
This thesis investigates the adoption rate of manufacturing strategy formulation processes and provides insights into why current formulation process workbooks are not widely adopted. A paradigm is developed to enhance the adoption of process workbooks in the manufacturing environment and attempts to bridge the gap between tried and tested processes and their practical application in manufacturing industry. Manufacturing strategy formulation processes have been developed to assist manufacturing companies in the development of manufacturing strategies. There is evidence that the adoption of these processes and the development of strategies within manufacturing industry are beneficial. However, some literature provides anecdotal evidence suggesting that adoption levels of these formulation processes are low. The research programme investigates if, and why, the adoption of manufacturing strategy formulation processes has been low. lndustrially based interviews have been used that confirm the low level of adoption of these processes. A variety of reasons have been identified. These mainly focus on the presentation and format of process workbooks. Several proposals are made to enhance the adoption of manufacturing strategy formulation processes. I particular, the research identifies four key areas that should be considered in the future presentation of manufacturing strategy formulation process. These key areas can be summarised as validity, attention, simplicity, and holistic perspective forming the basis of a paradigm to increase the use of workbooks and the adoption of strategy formulation processes by manufacturing managers. The findings of this research and the development of a paradigm offer practical assistance to bridge the gap between research activities and practitioner requirements. The paradigm has been evaluated by further interviews with industry practitioners and makes a useful contribution to the formulation and application of strategy in manufacturing industry.